Analisis BOR dan Dampaknya Terhadap Faktor 5M di Rumah Sakit Umum Daerah Cilacap - Putrilia, Maya; Hakim, Agya Osadawedya; Anggraeni, Okti; Fauzi, Harry (Akademi Perekam dan Informasi Kesehatan Imelda, 2025)
Efficiency is one of the performance parameters/indicators which theoretically underlies all the performance of an organization including in hospitals. One of the services provided in the hospital is hospitalization. To assess the efficiency of the hospital, you can use the Barber Johnson chart. In this graph there is an area called the area of ??efficiency. RSUD Cilacap is one of the hospitals belonging to the Regional Government of Cilacap Regency which in 2022 will still not meet the established Barber-Johnson standards. The purpose of this study was to analyze the efficiency of BOR at Cilacap Hospital in 2022 using the Barber-Johnson standard. This research method uses a descriptive qualitative approach. The variable used in this study in the processing of daily inpatient censuses. The results of the analysis are then linked to the impact of the Man, Method, Money, Machine, Material factors. The risults of the study exspained that the BOR in Cilacap Hospital did not meet the established efficient standars. The impact of BOR on the man factordid not really affect the hospital, the Money factor did not really effect the Cilacap Hosptal. The impact on the Machine factor makes the equipment in the hospital more durable, the impact on the method factor, namely the reporting system becomes not deal and the reduced indicators in regional development programs, the impact on the material factor causes wateful purchases of materials.